For each integer 1 ≤ j ≤ 2 0 1 7 , let S j denote the set of integers 0 ≤ i ≤ 2 2 0 1 7 − 1 such that ⌊ 2 j − 1 i ⌋ is an odd integer. Let P be a polynomial such that P ( x 0 , x 1 , … , x 2 2 0 1 7 − 1 ) = 1 ≤ j ≤ 2 0 1 7 ∏ ⎝ ⎛ 1 − i ∈ S j ∏ x i ⎠ ⎞ . Compute the remainder when ( x 0 , … , x 2 2 0 1 7 − 1 ) ∈ { 0 , 1 } 2 2 0 1 7 ∑ P ( x 0 , … , x 2 2 0 1 7 − 1 ) is divided by 2 0 1 7 .
This was proposed by A s h w i n S a h .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I don't understand what happened in first two paras... Which theorem has been applied HR.
Problem Loading...
Note Loading...
Set Loading...
The set of S j is made up of S j = [ 2 j − 1 , 2 ⋅ 2 j − 1 − 1 ] ∪ [ 3 ⋅ 2 j − 1 , 4 ⋅ 2 j − 1 − 1 ] . . . ∪ [ ( 2 2 0 1 8 − j − 1 ) 2 j − 1 , 2 2 0 1 8 − j ⋅ 2 j − 1 − 1 ] . If we let T j = ∏ i ∈ S j x i , then P ( x 0 , x 1 , . . . , x 2 2 0 1 7 − 1 ) = ∏ 1 ≤ j ≤ 2 0 1 7 ( 1 − T j ) . The polynomial is 1 if all T i are 0 and the polynomial is 0 if at least one T i is 1 . Thus, we need to count the number of permutations such that all T i are zero. We can use complementary counting and PIE. Let A i denote the set of permutations where T i = 1 and let P be the set of all permutations. We want to compute X = ∣ P ∣ − ∑ ∣ A i ∣ + ∑ ∣ A i ∩ A j ∣ − ∑ ∣ A i ∩ A j ∩ A k ∣ + . . . Now observe that ∣ S j ∣ = 2 2 0 1 6 for all j so ∣ A j ∣ = 2 2 2 0 1 6 .
Now let's consider ∣ A i ∩ A j ∣ . WLOG i < j . Let's look at S i and S j first. Notice that in each part of S j (and each "nonpart") half of it is taken up by parts of S i . Thus, S j actually fills in half of the gaps. So, there will be 2 2 0 1 6 + 2 2 0 1 5 numbers here in their union. These need to be equal to 1 . Thus, we obtain that ∣ A i ∩ A j ∣ = 2 2 2 0 1 5 .
By similar reasoning, we have that ∣ A a 1 ∩ A a 2 ∩ A a 3 ∩ . . . ∩ A a k ∣ = 2 2 2 0 1 7 − k .
So actually, we have that X = ∑ i = 0 2 0 1 7 ( − 1 ) k ( k 2 0 1 7 ) 2 2 2 0 1 7 − k ≡ 2 2 2 0 1 7 − 2 ( m o d 2 0 1 7 ) . Let's compute 2 2 2 0 1 7 in modulo 2 0 1 7 . We first compute 2 2 0 1 7 in modulo 2 0 1 6 . I think 2 0 1 6 = 2 5 ⋅ 3 2 ⋅ 7 .
So, let m = 2 2 0 1 7 we have
m ≡ 0 ( m o d 3 2 )
m ≡ 2 ( m o d 9 )
m ≡ 2 ( m o d 7 ) Now we use Chinese Remainder Theorem, uh m ≡ 2 ( m o d 6 3 )
m ≡ 1 2 8 ( m o d 2 ) 0 1 6 . Now by Fermat's Little Theorem, we want to reduce 2 1 2 8 in modulo 2 0 1 7 . Thus, the answer is that minus 2 to get 1 8 4 0